2021
DOI: 10.14336/ad.2020.0908
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Extracellular Vesicles Separated from Plasma of Former National Football League Players at Risk for Chronic Traumatic Encephalopathy

Abstract: Chronic Traumatic Encephalopathy (CTE) is a tauopathy that affects individuals with a history of exposure to repetitive head impacts, including National Football League (NFL) players. Extracellular vesicles (EVs) are known to carry tau in Alzheimer's disease and other tauopathies. We examined protein profiles of EVs separated from the plasma of former NFL players at risk for CTE. EVs were separated from the plasma from former NFL players and age-matched controls using size-exclusion chromatography. Label-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
(72 reference statements)
0
13
1
Order By: Relevance
“…Figure 1a shows a schematic outline of the EV isolation experimental set‐up. EVs were separated from the unfixed frozen brain tissue (0.6 g) based on our previous method with some modifications (Muraoka et al., 2020, 2021). The tissue was sliced with a razor blade into small sections 2−3 mm 3 on dry ice, and then dissociated in 4 mL Hibernate‐E medium (Cat# A1247601, Thermo Fisher Scientific) containing 75 U/mL collagenase type 3 (Worthington # CLS‐3, S8P18814) at 37°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1a shows a schematic outline of the EV isolation experimental set‐up. EVs were separated from the unfixed frozen brain tissue (0.6 g) based on our previous method with some modifications (Muraoka et al., 2020, 2021). The tissue was sliced with a razor blade into small sections 2−3 mm 3 on dry ice, and then dissociated in 4 mL Hibernate‐E medium (Cat# A1247601, Thermo Fisher Scientific) containing 75 U/mL collagenase type 3 (Worthington # CLS‐3, S8P18814) at 37°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…However, several studies have since identified total tau protein and/or phosphorylated tau associations with mild or isolated TBI events using CNS-derived exosome enrichment strategies. Elevated levels of exosome total tau has been observed in mild, moderate, severe, and repetitive TBI patients ranging from days to years after the initial injury ( 38 40 , 47 , 49 , 51 ). The consistency in findings of increased tau levels across TBI severity suggests tau is a relatively sensitive marker despite the heterogeneous nature of TBI presentations.…”
Section: Neurodegenerative Proteinsmentioning
confidence: 99%
“…Another preliminary study had shown that total exosomal tau levels significantly correlated with cognitive functioning as measured by short-term memory in retired professional football players (Stern et al, 2016). Studies involving proteomic analysis of CSF-derived and plasma-derived EVs from retired National football league (NFL) players who were at risk of developing CTE found a significant correlation between t-tau and p-tau181 levels in CSF, but not in a control group (Muraoka et al, 2019(Muraoka et al, , 2021.…”
Section: Evs As Potential Predictors Of Functional Outcomes In Tbimentioning
confidence: 99%
“…Several studies have found links between total tau protein or phosphorylated tau and mild, moderate to severe TBI incidents applying CNS-derived exosome enrichment methods. Despite the variability and heterogenicity in TBI presentations, exosomal total tau has been found to be augmented in mild, moderate, severe, and repetitive TBI patients from days to years after the initial injury (Stern et al, 2016 ; Kenney et al, 2018 ; Gill et al, 2018b ; Goetzl et al, 2019 , 2020 ; Muraoka et al, 2019 , 2021 ; Mondello et al, 2020 ), suggesting it to be relatively sensitive marker which exhibits both an acute and a chronic temporal course.…”
Section: Evs As Diagnostic and Therapeutic Conduits In Tbi: Examining...mentioning
confidence: 99%